2020
DOI: 10.3390/polym12081736
|View full text |Cite
|
Sign up to set email alerts
|

Surface Quality Evaluation of Removable Thermoplastic Dental Appliances Related to Staining Beverages and Cleaning Agents

Abstract: (1) Background: Thermoplastic materials are not inert and subject to changes in the oral environment, which affect their surface quality. Color stability and topographic characteristics of clear thermoplastic appliances are critical considerations. The study aimed to evaluate the optical changes and surface topography of different thermoplastic materials related to staining beverages and cleaning agents. (2) Methods: Thermoplastic polyethylene terephthalate glycol (PET-G) material specimens were selected for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 43 publications
0
26
0
6
Order By: Relevance
“…Studies of this type simulate the environment of the oral cavity through solutions of artificial saliva and exposure to highly pigmented foods such as wine, coffee, cola, tea and different cleaning methods [ 41 ]. The most recent data, in which both PET-G and polyurethane based aligners are used, agree in affirming that there are foods that stain more than others (above all black tea), that polyurethanes are more subject to color alterations, that even the surface analysis with a scanning electron microscope shows a greater alteration of the integrity of the material, and that this becomes all the more significant the longer the aligner is used (the aligners after two weeks show values of surface alteration above the threshold level of 0.20 μm) [ 30 , 42 ]. Other authors [ 31 , 32 , 43 ] found that material properties change during the wear-time, and this may affect treatment outcomes since the intraoral aging of clear aligners (regardless of the type of material they are made of) through biofilm modifications and oral environmental conditions might have an adverse effect on material properties and stability over the treatment time, compromising the force delivery capacity and treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of this type simulate the environment of the oral cavity through solutions of artificial saliva and exposure to highly pigmented foods such as wine, coffee, cola, tea and different cleaning methods [ 41 ]. The most recent data, in which both PET-G and polyurethane based aligners are used, agree in affirming that there are foods that stain more than others (above all black tea), that polyurethanes are more subject to color alterations, that even the surface analysis with a scanning electron microscope shows a greater alteration of the integrity of the material, and that this becomes all the more significant the longer the aligner is used (the aligners after two weeks show values of surface alteration above the threshold level of 0.20 μm) [ 30 , 42 ]. Other authors [ 31 , 32 , 43 ] found that material properties change during the wear-time, and this may affect treatment outcomes since the intraoral aging of clear aligners (regardless of the type of material they are made of) through biofilm modifications and oral environmental conditions might have an adverse effect on material properties and stability over the treatment time, compromising the force delivery capacity and treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Eight brands are mentioned in the scientific literature. Airnivol (AirNivol S.p.A, Navacchio di Cascina -Pisa, Italy) has been used in three comparative studies between systematics on fitting influenced by the thickness of the aligner, by exposure to the oral environment and in the study of the extrusion movement of the central incisor [ 29 , 30 , 53 ]. ALL IN (Micerium S.p.A., Avegno- Genova, Italy) and Arc Angel (Gruppo Dextra, Modena, Italy) have only been used in one study about the comparative analysis of the gap and thickness of different brands [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Means were compared by Scheffe's multiple range test for post hoc analysis at 95% probability level. The average color deference of ∆E*ab was permitted by less than 1.5 (Slight change) according to NBS 8,9) . Effect size 2.14 (Cohen's d) was calculated by following formula in pilot study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previously problems related to the sealants consist of low abrasion resistance, weak retention to the applied material, poor surface quality, and microcracks [ 38 , 39 ]. Further studies should be performed in order to investigate if surface conditioning before glazing increases the bond strength between the resin-composite CAD-CAM and the sealant, after aging procedures because resin-composite are expected to be hydrophilic [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%